9th AIAA Atmospheric and Space Environments Conference 2017
DOI: 10.2514/6.2017-4243
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Mixed-Phase Icing Cloud Simulations with Experiments Conducted at the NASA Propulsion Systems Laboratory

Abstract: This paper presents the evaluation of a numerical model for simulation of the icing cloud development at NASA Glenn Research Center's Propulsion Systems Laboratory (PSL). The model is helping the icing facility and the fundamental ice-crystal icing physics research team to better understand the complex interactions between the test parameters and have greater confidence in the conditions at the test section of the PSL tunnel. The model attempts to explain the observed changes in test conditions by coupling the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…(3). In a purely liquid cloud, the measurement from 2.1-mm and 0.5-mm cylindrical elements is less than what is measured by the CIKP 9 . Hence a water-catch efficiency (WE) term is applied to the actual LWC as seen in Eq.…”
Section: =mentioning
confidence: 61%
See 1 more Smart Citation
“…(3). In a purely liquid cloud, the measurement from 2.1-mm and 0.5-mm cylindrical elements is less than what is measured by the CIKP 9 . Hence a water-catch efficiency (WE) term is applied to the actual LWC as seen in Eq.…”
Section: =mentioning
confidence: 61%
“…The most recent joint NASA and NRC test 7 in March 2012 included a traversable total air temperature (TAT) & relative humidity (RH) probe 8 which allowed measurements at tunnel centerline. Subsequent modelling showed that a decreasing air temperature was due to the energy exchange from the partial evaporation of the cloud [9][10][11] . The temperature change was sometimes as much as several degrees Celsius, which is significant for icing tests, and measurements of the cloud-on conditions are continued to the present testing.…”
Section: Introductionmentioning
confidence: 99%
“…The model will be referred to as the Bartkus thermal model. Modifications [5] and advancements [6] to the Bartkus model were made to simulate the condition in the PSL. The ultimate goal of the model is to better understand the complex interactions between the test parameters and have greater confidence in the conditions at the icing tunnel's test section.…”
Section: Thermal Modelmentioning
confidence: 99%
“…This can lead to an alteration of the local static and total temperatures of the flow. Bartkus et al [5,6] reported on both experimental data obtained in the PSL and numerical data obtained using a thermal model that demonstrated changes in air temperature as a result of the thermal exchange with the icing cloud. This paper will provide an analysis of recently obtained data taken with the RFP in a series of ice cloud calibration and characterization tests performed in the PSL (see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Varying the plenum humidity varies the local wet bulb temperature, TWB. The wet bulb temperature affects the freeze-out of the cloud particles in the plenum, which is where the cloud is expected to have the greatest residence time 10 . The test points in Table 1 are arranged in order of decreasing TWB.…”
Section: T American Institute Of Aeronautics and Astronauticsmentioning
confidence: 99%